1982
DOI: 10.1002/ajim.4700030211
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in coalminers: Their relationship to the development of progressive massive fibrosis

Abstract: Sera from 2421 coalminers, representing all the radiological categories of pneumoconiosis, and from 260 healthy blood donors, as controls, were examined for antinuclear factor and rheumatoid factor. Antinuclear factors were present in 21.5% of sera from the controls and in 23.1 % from the coalminers' group. Rheumatoid factor was present in 5.3% of coalminers and as expected occurred particularly in the few men with progressive massive fibrosis who also had rheumatoid disease. The combined prevalence of both fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Antibody levels possessed no predictive value in the genesis of massive fibrosis (54). A parallel existed in respect to sandblasters' silicosis, in which high levels of ANA, RF and serum immunoglobulins were unrelated to the stage of disease, radiological progression, or decrement of lung function (55).…”
Section: Human Responsesmentioning
confidence: 99%
“…Antibody levels possessed no predictive value in the genesis of massive fibrosis (54). A parallel existed in respect to sandblasters' silicosis, in which high levels of ANA, RF and serum immunoglobulins were unrelated to the stage of disease, radiological progression, or decrement of lung function (55).…”
Section: Human Responsesmentioning
confidence: 99%
“…Studies show an association between chronic silicosis and autoimmune disease, such as systemic sclerosis, lupus erythematosus, rheumatoid arthritis, dermatomyositis, and vasculitis [ 1 , 2 , 3 , 4 , 5 , 6 ]. Epidemiological studies among coal miners with silicosis have demonstrated a high frequency of antinuclear antibodies and rheumatoid factor [ 7 ]. Exposure to silica may also be the prime factor of glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…An increased prevalence occurred with age at all levels of pulmonary involvement and there was no evidence that autoantibodies were of value in detecting men predisposed to the development of massive pulmonary fibrosis, other than those with clinically manifest rheumatoid disease [45], Similarly, in sub jects exposed to silica, there was no signifi cant correlation between any humoral immu nological abnormality and radiographic changes or declines in pulmonary function [46] . Nor were any such correlations found in asbestos workers with and without asbestosis [47] , Cystic fibrosis patients exhibit circulating immune complexes in 25-47% of patients studied [48,49].…”
Section: Human Immune Complex Diseases: Real and Putativementioning
confidence: 99%